Identifikasi dan Analisis Rumah Sehat Berdasarkan Standar Kementerian Kesehatan (Studi Kasus: Gampong Mulia, Kota Banda Aceh) - Arisaputri, Sri Batara Nurfajri; Elysa Wulandari; Nini Rahayu Nur; Shabira Salsabila (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
A healthy home is a crucial indicator in establishing liveable settlements and supporting the overall well-being of residents. This study aims to identify and analyse the condition of healthy homes in Gampong Mulia, Kuta Alam Subdistrict, Banda Aceh City, based on indicators established by the Indonesian Ministry of Health. The location was selected due to its dense urban character and its status as a recipient area for post-tsunami housing assistance following the 2004 disaster. Over time, many of these aid houses have been repurposed as rental housing, leading to variations in physical conditions and resident behaviours. A descriptive quantitative method was applied, using field surveys and interviews. Twenty-five sample houses across five village zones were assessed based on three components: physical condition, sanitation facilities, and resident behaviour. The results show that 88% of the houses meet the criteria for healthy homes (total score ≥ 1,068), while 12% fall below the standard, all of which are located in Tgk. Di Leupeu Hamlet—an area with a notable concentration of rental units. The highest average score was for resident behaviour (425), followed by physical condition (534), and sanitation (322). This research highlights the need for targeted interventions, particularly in post-disaster communities, to support sustainable and equitable settlement planning.